Correlation between the strength of conjugation and spin–spin interactions in stable diradicaloids. Issue 31 (25th March 2020) - Hu, Xiaoguang; Chen, Hanjiao; Xue, Guodong; Zheng, Yonghao
Abstract : Blatter based diradicaloids with p -diphenyl, fluorenyl and naphthyl bridges exhibit bridge dependent magnetic and optical properties. Abstract : Diradicaloids are emerging materials for organic electronics and spintronics, and therefore understanding the correlation between their physical properties and the strength of conjugation effect is important. Herein, we report a systematic study of three Blatter based diradicaloids with different conjugated bridges such as twisted p -diphenyl (DPh-D ), locked fluorenyl (FDT ) and fused naphthyl (Nap-D ). All these molecules possess an open-shell singlet ground state. Their diradical character decreases from DPh-D to Nap-D (0.44 to 0.14). Meanwhile, their corresponding singlet–triplet energy gaps increase from −1.27 to −1.54 kcal mol −1 . However, the magnetic properties in the solid state are heavily affected by molecular stacking, the close 1-D chain π-π stacking in FDT  gives a high-spin quintet state. Overall, we have observed that the better the conjugation the stronger the spin–spin interaction in diradicaloids, which also significantly influence their physical properties.